Pelaksanaan Zakat Penangkaran Sarang Burung Walet Di Desa Srimulyo Kecamatan Tungkal Jaya Kabupaten Musi Banyuasin Provinsi Sumatera Selatan - Linta Kristiana; Arsa Arsa; Ahmad Syukron Prasaja (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
The background of this research is the implementation of zakat on the breeding of swallow's nests in the village of Srimulyo, Tungkal Jaya District, Musi Banyuasin Regency, South Sumatra Province, whose practices are not yet in accordance with Islamic regulations. This type of research is field research using descriptive qualitative methods. This research was conducted in Srimulyo Village, Tungkal Jaya District, Musi Banyuasin Regency, South Sumatra Province, using a normative and sociological approach, using primary and secondary data sources. Data collection techniques are observation, interviews, and documentation. Data analysis techniques are data collection, data reduction, data presentation, then drawing conclusions.The results of the study show that the implementation of zakat on the breeding of swallow's nests in Srimulyo Village, Tungkal Jaya District, Musi Banyuasin Regency, South Sumatra Province has quite a large potential for zakat. However, this was not implemented because it had various obstacles in its implementation, such as: swallow nest breeders did not pay zakat because they lacked literacy about swallow nest zakat, there was no amil zakat institution that socialized it to the village, some of them paid zakat with a rate of 2, 5% follows the zakat property which is paid once a year. Even though the rate they should spend on the results of breeding swallow's nests is 5% each time a sale is made of total net income. On the other hand, it turns out that there are still many breeders who are reluctant to pay zakat, there are also those who do not recommend giving zakat at all.